Indigenising the Curriculum or Negotiating the Tensions at the Cultural Interface? Embedding Indigenous Perspectives and Pedagogies in a University Curriculum - Williamson, Jane; Dalal, Priya (The Australian Journal of Indigenous Education, 2007)
Abstract Attempts to Indigenise the curriculum run the risk of implying the application of an “impoverished” version of “Aboriginal pedagogy” and the promotion of corrupted understandings of Indigenous knowledge (Nakata, 2004, p. 11). What is required, Nakata (2004, p. 14) argues, is a recognition of the complexities and tensions at cross-cultural interfaces and the need for negotiation between “Indigenous knowledge, standpoints or perspectives” and Western disciplinary knowledge systems such that meanings are reframed or reinterpreted. Attending to these cross-cultural negotiations and the pedagogical practices they imply are profoundly challenging for both Indigenous and non-Indigenous educators. This paper focuses on a project at Queensland University of Technology (QUT) which seeks to embed Indigenous perspectives in Humanities and Human Services curricula. It outlines the curriculum framework which was developed to guide the curriculum redesign in its initial phases. This is followed by a discussion of current research that has been concerned to identify material that can support the renegotiations of curricula endorsed by Nakata’s work. The research findings indicate that it is possible to identify a number of pedagogical approaches that can assist that process. Such approaches recognise various levels of engagement beyond the “intellectual”; they insist on a consistent unsettling of Western authority; they acknowledge Indigenous positions/positioning; and require critical self-reflection.